2002
DOI: 10.1074/jbc.m108607200
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS4 Cleaves at the Aggrecanase Site (Glu373-Ala374) and Secondarily at the Matrix Metalloproteinase Site (Asn341-Phe342) in the Aggrecan Interglobular Domain

Abstract: Aggrecan is the major cartilage hyalectan (1), which, together with the collagen network, provides this tissue with its unique mechanical properties of compressibility and stiffness (2-4). Extraction of aggrecan in its native form (5) and subsequent structural analysis (6) have revealed that the molecular organization of aggrecan is perfectly suited to its central functional role in articular cartilage. The N-terminal region of aggrecan is composed of two globular domains (G1 1 and G2) separated by the intergl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 49 publications
2
63
0
1
Order By: Relevance
“…In this context, whereas aggrecanase activity is responsible for generating most of the "free" G1 (i.e., G1-NITEGE 373 ) that is detectable in human synovial fluid, MMP-generated G1 (i.e., G1-VDIPEN 341 ) can be detected in synovial fluid from older individuals and from patients with end-stage OA (13), although this likely represents secondary "trimming" of preexisting G1-NITEGE 373 by MMPs (37). It has also been demonstrated that relatively high concentrations of ADAMTS-4 can cleave aggrecan secondarily, at the Asn 341 -Phe 342 site (21). However, given the correlation between the release of sGAG and G1-NITEGE 373 in response to ADAMTS-4 or ADAMTS-5 treatment observed in the current study, it is unlikely that G1-VDIPES 341 fragments were generated under the conditions tested.…”
mentioning
confidence: 47%
“…In this context, whereas aggrecanase activity is responsible for generating most of the "free" G1 (i.e., G1-NITEGE 373 ) that is detectable in human synovial fluid, MMP-generated G1 (i.e., G1-VDIPEN 341 ) can be detected in synovial fluid from older individuals and from patients with end-stage OA (13), although this likely represents secondary "trimming" of preexisting G1-NITEGE 373 by MMPs (37). It has also been demonstrated that relatively high concentrations of ADAMTS-4 can cleave aggrecan secondarily, at the Asn 341 -Phe 342 site (21). However, given the correlation between the release of sGAG and G1-NITEGE 373 in response to ADAMTS-4 or ADAMTS-5 treatment observed in the current study, it is unlikely that G1-VDIPES 341 fragments were generated under the conditions tested.…”
mentioning
confidence: 47%
“…The zymogen form of the protein was predicted to have a molecular weight of 90.2 kd, and the furin-cleaved isoform was predicted to have a molecular weight of 67.9 kd (9). Furin-cleaved recombinant human ADAMTS-4 (rHuADAMTS-4) has been reported as having a molecular weight of 68 kd (10) and a molecular weight of 70 kd (11). The thrombospondin motif of ADAMTS-4 is required for aggrecan binding and cleavage (mediated via the GAG chains of aggrecan) (12).…”
mentioning
confidence: 99%
“…Compared with the constitutively expressed ADAMTS5, ADAMTS4 is induced dramatically by IL-1, tumor necrosis factor ␣, and type ␤ transforming growth factor in rheumatoid arthritis (RA) and osteoarthritis, suggesting that ADAMTS4 plays a more important role in cartilage breakdown (6,7). In addition to arthritic joints, ADAMTS4 is also expressed in ovary, spinal cord, uterus, brain, and heart and can mediate the degradation of other extracellular matrices such as versican and brevican (4,8). Although the biochemical properties of ADAMTS4 are well characterized, the cellular mechanisms by which ADAMTS4 is activated remain largely unknown.…”
mentioning
confidence: 99%